The impacts of mining on soil pollution with metal(loid)s in resource-rich Mongolia - Pecina, Václav; Juřička, David; Hedbávný, Josef; Klimánek, Martin; Kynický, Jindřich; Brtnický, Martin; Komendová, Renata (NATURE PORTFOLIO, 2023)
As Mongolia is considered one of the most resource extraction-dependent countries globally, significant mining-related environmental and human health risks are expected. The aim of this study was to (I) assess the impacts of mining on soil pollution with metals in Mongolia's key coal mining towns (Baganuur, Nalaikh and Sharyn Gol) and (II) review the current knowledge on soil pollution with metal(loid)s and related health risks in Mongolia. The results showed predominantly low soil contents of Cd, Cu, Pb and Zn and a related absence of severe pollution and potential health risk in the coal mining towns. Urban design, rather than the presence of mines, controlled the pollution distribution. Despite the methodological shortcomings of several studies on soil pollution in Mongolia, their results suggest a similarly low threat in the three largest cities (Ulaanbaatar, Darkhan, Erdenet) and several mining areas. While the generally highlighted risk of As seems like an artificially escalated issue, the content of Cr in urban soil may be a neglected threat. Further pollution research in Mongolia should focus on street dust and drinking water pollution.

As Mongolia is considered one of the most resource extraction-dependent countries globally, significant mining-related environmental and human health risks are expected. The aim of this study was to (I) assess the impacts of mining on soil pollution with metals in Mongolia's key coal mining towns (Baganuur, Nalaikh and Sharyn Gol) and (II) review the current knowledge on soil pollution with metal(loid)s and related health risks in Mongolia. The results showed predominantly low soil contents of Cd, Cu, Pb and Zn and a related absence of severe pollution and potential health risk in the coal mining towns. Urban design, rather than the presence of mines, controlled the pollution distribution. Despite the methodological shortcomings of several studies on soil pollution in Mongolia, their results suggest a similarly low threat in the three largest cities (Ulaanbaatar, Darkhan, Erdenet) and several mining areas. While the generally highlighted risk of As seems like an artificially escalated issue, the content of Cr in urban soil may be a neglected threat. Further pollution research in Mongolia should focus on street dust and drinking water pollution.
The impacts of mining on soil pollution with metal(loid)s in resource-rich Mongolia
Keywords: urban soil; coal; health risk assessment; contamination; potentially toxic elements; urban soil; coal; health risk assessment; contamination; potentially toxic elements